Explanation of an Effective Reward Pattern for Civil Servants of Iran, Considering the Total Reward Approach (مطالعات مدیریت بهبود و تحول, 2011)
Every organization wants to attract, retain and motivate its employees.Many believe that such desire is an initial purpose of any rewardprogram. The total rewards approach provides organizations with atotal solution. By taking Armstrong’s total rewards approach,organizations can achieve the best mix of monetary and non-monetaryrewards. In this research, it is attempted to offer an effective rewardpattern for civil servants regarding the total reward approach. Our datawere gathered by random sampling from the employees of ExportDevelopment Bank of Iran and were analyzed using SPSS 16 andLISREL 8/51. Results of the research show that there is a positivemeaningful correlation among elements of total reward, motivationand performance. Also, there is a positive meaningful causalrelationship between elements of the total reward and motivation, andbetween elements of total reward and performance. There is found nocausal relationship between motivation and performance. Meanwhile,among the elements of total reward, the individual-transactionalrewards and communal-relational rewards have more effect on thedependent variables. It is important to note that the aforesaid relationswere provided by the structural equation modeling.